Primary Sjögren's syndrome 1976–2005 and associated interstitial lung disease: a population-based study of incidence and mortality. Issue 11 (25th November 2013) - Nannini, Carlotta; Jebakumar, Adlene J; Crowson, Cynthia S; Ryu, Jay H; Matteson, Eric L
Abstract : Objective: A very few studies describe the epidemiology of primary Sjögren's syndrome (pSS). The reported frequency of pulmonary involvement in pSS varies widely depending on the detection method employed, and consists mainly of various forms of airways disease. We aimed to evaluate the incidence and mortality of pSS and of lung disease in pSS, focusing on interstitial lung disease (ILD). Methods: A population-based incidence cohort of patients diagnosed with pSS in 1976–2005 was assembled. Diagnosis was based on the 2002 American-European Consensus Group criteria for pSS. Cumulative incidence adjusted for the competing risk of death was estimated. A Cox model with a time-dependent covariate was used to determine the incidence and the standardised mortality HR of pSS. Results: 85 patients with pSS were identified (mean age 59.9 years; 91% women). The annual incidence of pSS was 4.2, 95% CI (3.3 to 5.1)/100 000 population and it increased with higher age at pSS diagnosis (18–44 years: 2.1/100 000 vs ≥75 years: 12.3/100 000). Standardised mortality ratio in pSS compared with the general population was 0.92, 95% CI (0.57 to 1.41). A total of 105 patients with pSS and ILD were identified (mean age 58.1 years; 91% women). Among patients with pSS without prior ILD, the cumulative incidence of ILD in patients with pSS was 10% (±3%) at 1 year after diagnosis of pSS and increased to 20% (±4%) by 5 years after pSS. The development of lung disease in pSS was associated with poor survival (HR 2.16; 95% CI 0.99 to 4.74). Conclusions: pSS incidence seems to be almost the same as was reported in a previous study conducted among Olmsted County Minnesota population. Survival among patients with pSS and general population does not differ substantially. However, patients with pSS who have ILD likely have increased premature mortality.